2018
DOI: 10.1002/chem.201703971
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient endo Cycloisomerization of Terminal Alkynols Catalyzed by a New Ruthenium Complex with 8‐(Diphenylphosphino)quinoline Ligand and Mechanistic Investigation

Abstract: Several new ruthenium complexes supported by the P,N-donor ligand 8-(diphenylphosphino)quinoline (DPPQ) were synthesized, including [RuCl (DPPQ) ] (1), [Ru(μ-Cl)(DPPQ) ] (BPh ) (2), and [RuCl(DPPQ) Py](BF ) (3). Complex 2, with only 1 mol % loading, was found to be catalytically active for the endo cycloisomerization of various terminal alkynols to endo-cyclic enol ethers in moderate to excellent yields. In particular, the 7- and 8-endo heterocyclization can be achieved efficiently to give the seven-membered 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 127 publications
(109 reference statements)
2
14
0
Order By: Relevance
“…Cai et al illustrated that the cyclization selectivity can be shifted reliably in favor of the endo-dig cyclizations by changing the reaction mechanism [78]. The 5, 6, 7, and 8-endo-dig cycloisomerizations of terminal alkynols are possible under Ru-catalysis due to the formation and trapping of the Ru-vinylidene intermediate.…”
Section: Vinyl Ether Generation From Alkynesmentioning
confidence: 99%
“…Cai et al illustrated that the cyclization selectivity can be shifted reliably in favor of the endo-dig cyclizations by changing the reaction mechanism [78]. The 5, 6, 7, and 8-endo-dig cycloisomerizations of terminal alkynols are possible under Ru-catalysis due to the formation and trapping of the Ru-vinylidene intermediate.…”
Section: Vinyl Ether Generation From Alkynesmentioning
confidence: 99%
“…8-Quinolylphosphanes are competent ligands for various functional coordination compounds, because they consist of a strongly -donating phosphane donor group and a -conjugated quinoline moiety and form a stable planar fivemembered chelate ring on coordination to a metal center (Cai et al, 2018;Hopkins et al, 2019;Scattolin et al, 2017). In one of our previous studies, it was revealed that 8-(diphenylphosphanyl)quinoline (PQ H ) in the simplest dichloridopalladium(II) complex, [PdCl 2 (PQ H )] (3), exhibits a strong trans influence of the diphenylphosphanyl donor group and an intermolecularstacking interaction between the quinoline ring systems (Suzuki et al, 2015).…”
Section: Chemical Contextmentioning
confidence: 99%
“…In 2018, Wen and co-workers reported cycloisomerizations of alcohol-tethered alkynes for oxacyclesw ith different ring sizes (5-to 8-membered) by employing Ru catalysts bearing 8-(diphenylphosphino)quinoline (DPPQ) (Scheme 10). [18] The Ruoxacarbene complexes isolated from the reactions served as evidencefor the Ru-vinylidene intermediacy.…”
Section: Catalytic Ru II -Mediated Cyclizations Of N/o-functionalizedmentioning
confidence: 99%